Le conte populaire et ses approches méthodologiques - Guilbert, Lucille (Ethnologies, 1981)
AbstractThe study of folktales is inseparable from the history of folklore studies. An incessant to-and-fro between the raw material - collected oral tales - and critical concerns - the different methodological approaches - demands attention to enrich and enhance our understanding. A close examination of the methodological approaches of the last hundred years reveals the complementarites of the different methods, their convergences in spite of the external oppositions strongly proclaimed by the proponents of the historico-geographic school, functionalism, structuralism. This methodological inquiry highlights the necessity to choose not one method, but rather to confront one with the others in a dialogue on the same material because each school represents a logical phase in the analysis of a story. Finally, following upon a discussion - in Structural Models in Folklore by Elli Köngas-Maranda and Pierre Maranda - the author formulates new models which, simple and adaptable, take into account ail the approaches simultaneously and permit observation of the principle of transformation at work in the narrative.